2022
DOI: 10.1063/5.0082624
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of laminar-to-turbulent transition in pipe flow

Abstract: This paper describes an experimental study of the unforced laminar-to-turbulent transition in pipe flow. Two pipes with different length-to-diameter ratios are investigated, and the transition phenomenon is studied using pressure measurements and visual observations. The entropy change and force balance are examined, and the peak powers are measured through fast Fourier transform analysis at various Reynolds numbers. Visual observations show that the flow structure changes at the Reynolds numbers corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In Pipe C, the factor decreased at approximately ReD=1600. In a previous study, the factor deceased between ReD=1200 and 12 000 [11]. Patel and Head reported that the coefficient deviated at ReD=1700 and returned at ReD=30000 [22].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In Pipe C, the factor decreased at approximately ReD=1600. In a previous study, the factor deceased between ReD=1200 and 12 000 [11]. Patel and Head reported that the coefficient deviated at ReD=1700 and returned at ReD=30000 [22].…”
Section: Resultsmentioning
confidence: 86%
“…The measured pressure was analysed using a fast Fourier transform, and a power peak appeared at ReD=1800 in the downstream pipe. In Pipe C and the ordinary pipe [11], the peak appeared at ReD=1200. The flow condition for the transition was different from that in ordinary pipe flow at low Reynolds numbers.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The movement of particles in the fluid forms a boundary layer due to friction between particles. The boundary layer divides fluid flow into laminar, transitional, and turbulent flow (Hattori et al, 2022). The regular and parallel movement of particles is called laminar flow (Committee, 2019).…”
Section: A Introductionmentioning
confidence: 99%